Exome sequencing identifies a novel UNC5D mutation in a severe myopic anisometropia family: A case report. Issue 24 (June 2017) - Feng, Lei; Zhou, Daizhan; Zhang, Zhou; He, Lin; Liu, Yun; Yang, Yabo
Abstract: Introduction: Severe myopic anisometropia has been identified to have heritability, but the pathogenesis of anisometropia still remains obscure. Case description: Here, we presented a Chinese severe myopic anisometropia family with 5 members affected. Though using the exome sequencing, we identified a novel mutation in the UNC5D gene (c.1297C>T, p.R433C), which was predicted to have a damage effect on the protein function and kept highly conserved throughout evolution across species. As previously described, the UNC5D gene belongs to the UNC5 protein family and may have functions to regulate neuronal migration, axon guidance, and cell survival. The expression of UNC5D was also co-located at the visual areas of the mouse cortical regions at early postnatal ages. Conclusion: Our data provide the first evidence for involvement of UNC5D gene in the severe myopic anisometropia. Abstract : Supplemental Digital Content is available in the text